Unraveling pleiotropic effects of rifampicin by using physiologically based pharmacokinetic modeling: Assessing the induction magnitude of P‐glycoprotein-cytochrome P450 3A4 dual substrates - Xian Pan; Shinji Yamazaki; Sibylle Neuhoff; Mian Zhang; Venkatesh Pilla Reddy (Wiley, 2021)
Abstract Rifampicin induces both P‐glycoprotein (P‐gp) and cytochrome P450 3A4 (CYP3A4) through regulating common nuclear receptors (e.g., pregnane X receptor). The interplay of P‐gp and CYP3A4 has emerged to be an important factor in clinical drug-drug interactions (DDIs) with P‐gp-CYP3A4 dual substrates and requires qualitative and quantitative understanding. Although physiologically based pharmacokinetic (PBPK) modeling has become a widely accepted approach to assess DDIs and is able to reasonably predict DDIs caused by CYP3A4 induction and P‐gp induction individually, the predictability of PBPK models for the effect of simultaneous P‐gp and CYP3A4 induction on P‐gp‐CYP3A4 dual substrates remains to be systematically evaluated. In this study, we used a PBPK modeling approach for the assessment of DDIs between rifampicin and 12 drugs: three sensitive P‐gp substrates, seven P‐gp-CYP3A4 dual substrates, and two P‐gp-CYP3A4 dual substrates and inhibitors. A 3.5‐fold increase of intestinal P‐gp abundance was incorporated in the PBPK models to account for rifampicin‐mediated P‐gp induction at steady state. The simulation results showed that accounting for P‐gp induction in addition to CYP3A4 induction improved the prediction accuracy of the area under the concentration‐time curve and maximum (peak) plasma drug concentration ratios compared with considering CYP3A4 induction alone. Furthermore, the interplay of relevant drug‐specific parameters and its impact on the magnitude of DDIs were evaluated using sensitivity analysis. The PBPK approach described herein, in conjunction with robust in vitro and clinical data, can help in the prospective assessment of DDIs involving other P‐gp and CYP3A4 dual substrates. The database reported in the present study provides a valuable aid in understanding the combined effect of P‐gp and CYP3A4 induction during drug development.